A preliminary flora survey in Gunung Kajang, Pulau Tioman, Pahang Darul Makmur, Malaysia - Mohd Norfaizal, G.; Masrom, H.; Omar, Y.; Aishah-Farhana, S. (Penerbit Universiti Kebangsaan Malaysia, 2014)
Gunung Kajang is one of the main area in Pulau Tioman, Pahang Darul Makmur. It is therefore, important to study her ecosystem and documenting various existing biodiversity components for management and conservation purposes. The Management and Utilization of Biological Resources Unit from Strategic Resources Research Centre (SR), MARDI Headquarters was tasked with documenting the rare and wild edible fruit species from the region and collecting the wild genetic resources of plants from this area for conservation purpose. From this survey, 51 families of flowering plants were identified, consists of 131 species, followed by monocotyledons with 11 families and 32 species. On the other hand, gymnosperm was represented by 3 species only, namely Agathis borneensis, Gnetum latifolium and Podocarpus polystachus. There were 26 species of rare and wild edible fruit species that are important for the food security and food sources for the wild animals community here. Many wild fruit species found are not known and are underutilised. Information on their potential health benefits is critical in efforts at promoting these fruits. This paper provides a preliminary checklist of rare and wild fruit trees recorded following a survey carried out from 5 – 10 April 2011.